PENGEMBAHAN BAHAN AJAR DALAM BENTUK BUKU SAKU PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR - Nurfitria Sari; Rasmiwetti Rasmiwetti; Abdullah Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This development research aims to produce a pocket book on the subject of atomic structure and the periodic system of elements. The method used is the Research and Development (R&D) method with the ADDIE development model. Broadly speaking, the stages of research and development include Analysis (analysis stage), Design (design stage), Development (development stage), Implementation (implementation stage), and Evaluation (evaluation stage). This research was carried out until the development stage and then continued with one-on-one trials and user response trials. The resulting product is a valid pocket book based on content feasibility aspects, linguistic feasibility aspects, presentation feasibility aspects, and graphic feasibility aspects. The average score of the four aspects of pocket book feasibility in a row are 97.2%, 96.9 92.8%, and 97.6%. So the overall average score of validation is 96.1% with valid/feasible criteria. The results of trials on teachers and students obtained an average percentage of 95.8% by teachers and 95.9% by students with very good criteria.Key words: Research and Development, ADDIE, Teaching Materials, Pocket Books, Atomic Structure and Periodic System of Elements